In Vitro Study on Apoptosis Induced by Strontium-89 in Human Breast Carcinoma Cell Line. (9th June 2011) - Wang, Cheng; Wang, Jing; Jiang, Han; Zhu, Min; Chen, Baoguo; Bao, Weiguang
Abstract : Many radiopharmaceuticals used for medical diagnosis and therapy are beta emitters; however, the mechanism of the cell death caused by beta-irradiation is not well understood. The objective of this study was to investigate the apoptosis of human breast carcinoma MCF-7 cell lines induced by Strontium-89 ( 89 Sr) and its regulation and control mechanism. High-metastatic Breast Carcinoma MCF-7 cells were cultured in vitro using 89 Sr with different radioactive concentration. The inhibition rate of cell proliferation was measured by MTT color matching method. The cell cycle retardation, apoptosis conditions, mitochondrion transmembrane potential difference and Fas expression were tested and analyzed. The genes P53 and bcl-2 expressions was also analyzed using immunity histochemical analysis. After being induced by 89 Sr with various of radioactive concentration, it was found that the inhibition of cell proliferation of MCF-7 cells was obviously, the retardation of cell cycle occurred mainly in G2-M. It was also found that the obvious apoptosis occurred after being induced by 89 Sr, the highest apoptosis rate reached 46.28%. The expressions of Fas acceptor and P53 gene increased, while bcl-2 gene expression decreasesd. These findings demonstrate that in the ranges of a certain radioactive concentration, the inhibition rate of MCF-7 cell proliferation and retardation of cell cycle had positive correlation with the concentration of 89 Sr. And the mitochondrion transmembrane potential decrease would induce the apoptosis of MCF-7 cell notably, which were controlled by P53 and bcl-2 genes, involved with the Fas acceptor.